2018
DOI: 10.1080/13607863.2018.1544207
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the implementation of the Dutch combined Meeting Centres Support Programme for family caregivers of people with dementia in Italy, Poland and UK

Abstract: Objectives: The MEETINGDEM research project aimed to implement the combined Dutch Meeting Centre Support Programme (MCSP) for community-dwelling people with dementia and caregivers within Italy, Poland and UK and to assess whether comparable benefits were found in these countries as in the Netherlands. Method: Nine pilot Meeting Centres (MCs) participated (Italy-5, Poland-2, UK-2). Effectiveness of MCSP was compared to usual care (UC) on caregiver outcomes measuring competence (SSCQ), mental health (GHQ-12), e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 26 publications
(24 reference statements)
1
28
0
Order By: Relevance
“…The benefits of such communitybased initiatives are now being recognised. [12][13][14][15][16] There is evidence that regular social activity, where people are able to leave their homes and gather together in a communal setting on a frequent and ongoing basis, can be helpful both for people living with dementia and the people who care for them. 12 13 17-19 With care systems unprepared for the forecasted UK doubling of the number of people living with dementia (1.6 million) and tripling of social care costs by 2040, 20 improving provision of evidencebased community initiatives for people with dementia, and their families, is imperative.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of such communitybased initiatives are now being recognised. [12][13][14][15][16] There is evidence that regular social activity, where people are able to leave their homes and gather together in a communal setting on a frequent and ongoing basis, can be helpful both for people living with dementia and the people who care for them. 12 13 17-19 With care systems unprepared for the forecasted UK doubling of the number of people living with dementia (1.6 million) and tripling of social care costs by 2040, 20 improving provision of evidencebased community initiatives for people with dementia, and their families, is imperative.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The research question was developed during the authors' previous work with community interventions (eg, but not limited to, Meeting Centres) 12 13 and the practical problems encountered with sustaining such interventions expressed both by personnel and by members of the public attending. This review mainly involved the gathering of secondary data so did not involve patients or public directly as study participants.…”
Section: Patient and Public Involvementmentioning
confidence: 99%
“…This combined form of support is highly appreciated by people with dementia and informal caregivers, and both benefit from it. This is evident not only from the great increase in the number of Meeting Centers over the past 25 years (there are now 163 centers across the Netherlands and about 25 in other countries in and outside Europe) but also from repeated scientific research 10–16. Several studies have shown that the users of the Meeting Centers are almost unanimously (very) satisfied with the offer13,17 and that compared to regular day care, the participants with dementia using MCSP have fewer behavioral and mood problems and higher self-esteem,10,11,15 their informal caregivers feel more competent, nursing home admission is postponed,12 and lonely informal caregivers have fewer health complaints 14.…”
Section: Introductionmentioning
confidence: 99%
“…Higher attendance levels were associated with greater neuropsychiatric symptom reduction and increased feelings of support 14. Carers experienced less burden than those receiving usual care 15…”
Section: Introductionmentioning
confidence: 97%